A scoping review of the existing evidence linking school food procurement contract type with school food provision - Nicola Nixon; Maria Bryant; Laura Sheard; Louise Padgett; Bob Doherty (PLoS ONE, 2025)
Objective School food and catering constitutes the largest area of public sector food spend in the UK, with the potential to influence health on a population scale. This review sought to understand and map the existing evidence linking school meals contracts for food procurement with the quality of food provided and health and academic outcomes for school children. Design A scoping review of the peer reviewed and grey literature published between 1988 and 2023 was conducted. The strategy searched in Medline, Web of Science, Scopus, ERIC and Google, using key words related to population, exposure and outcomes. Setting UK and International. Participants School meal services. Results Thirty documents were included representing 16 papers, 3 books and 11 reports. Documents revealed a complex and fragmented school meal provision system and inconsistent evidence relating to the outcomes of interest. Most studies focused on sustainability or nutrition/ guideline compliance and the main types of food providers discussed were commercial contractors, local authorities and in house catering. However, there was a lack of clarity in contract specifications and definitions of quality and concerns over compliance monitoring and financial viability impacting quality. We found no substantial body of peer reviewed research linking school food procurement contract type with food quality or outcomes of interest. Conclusions The lack of research in this area (and conflicting findings) meant that it was impossible to draw robust conclusions on the benefits of using any particular contract provision type over another. Given the magnitude of public sector spending and the need for urgent improvements to the dietary health of the nation, this presents a significant gap in our knowledge.